Y‐ and H‐Shaped Amphiphilic PEG–PCL Block Copolymers Synthesized Combining Ring‐Opening Polymerization and Click Chemistry: Characterization and Self‐Assembly Behavior. Issue 12 (14th May 2014) - Tirino, Pasquale; Conte, Claudia; Ordegno, Monica; Palumbo, Rosario; Ungaro, Francesca; Quaglia, Fabiana; Maglio, Giovanni
<x xml:space="preserve">Abstract</x> The aim of this work is to obtain poly(ethylene glycol) (PEG) (hydrophilic)–poly(ε‐caprolactone) (PCL) (hydrophobic) block copolymers with different architectures to point out the influence of this parameter on the water self‐assembly behavior. The key role in the copolymer synthesis is played by a click chemistry strategy based on Huisgen cycloaddition, between the alkyne and azide terminal groups of different polymeric segments. The obtained copolymers are characterized by NMR, Fourier transform IR (FTIR) spectroscopy, differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD), and size‐exclusion chromatography (SEC) techniques. In an aqueous environment, the hydrophilic and hydrophobic blocks of the amphiphilic copolymers form the corona and the core of the nanoaggregates, respectively, giving different morphologies as a function of the copolymer architecture. Furthermore, dynamic light scattering (DLS), transmission electron microscopy (TEM), and zeta potential measurements reveal promising features as nanocarriers of lipophilic molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>